Potential of energy efficiency in ceramic industries - Narayanamoorthy, Thirupathi Rao (2004)
In year 1994 Asian Development Bank and Ministry of Energy, Telecommunications and Posts Malaysia have produced an economic analysis and recommendation report on Energy Efficiency in Malaysian Industries. By using this report's recommendations as the stepping stone, an effort was made to study the potential of EE in ceramic Industries. A common analysis methodology was suggested to suite the whole industry nation wide. At the end of this work a special focus is given to the Non-Metallic Sector or more specifically ceramic industry as a case study sample in identifying the potential of EE. According to the above mentioned report, ceramic industry falls as one of the highest energy consumer and energy intensive industry. This study is based on identifying the potential of EE in the Malaysian industry sector and ranking the best options available to implement energy efficiency measures. Malaysian Energy Center (Pusat Tenaga Malaysia, PTM), has been very helpful in providing the necessary energy audit data. A thorough understanding of the industrial process flow is necessary in order to plan an energy efficient measure. Literature reviews, plant visits and software based analysis were critical aspects of the methodology used in this project. The data were analyzed using software called Save-X. The priority of available EE options were weighed according to the pay-back period (PBP) and benefit to cost ratio (BCR). As a conclusion, industries with similar facilities as the case study sample (ceramic) can apply the EE measures and analysis technique to view the potential EE. After benchmarking with international frontrunner there seems to be a huge potential of EE even after implementing all the EE measures recommended by the locally conducted energy audit report. More efforts should be taken to take a glance into frontrunners EE operations and try to implement here in Malaysia. Eventually this will lead us to more EE Malaysian Industries and more benefits to the environment in terms of less fuel are burnt to produce inefficient energy use.